Resilience among University Students Memorizing the Qur’an: The Role of Self-Regulated Learning in a Mixed-Methods Study - Satria Amir Makmun Gunawan; Rahmat Aziz; Esa Nur Wahyuni (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
The phenomenon of university students memorizing the Qur’an has attracted scholarly attention because they must maintain memorization consistency while managing academic demands, assignments, organizational activities, and social pressures. These conditions may lead to fatigue, boredom, decreased motivation, and the desire to stop memorizing, indicating challenges related to resilience. This study aims to assess the levels of self-regulated learning and resilience and examine the effect of self-regulated learning on the resilience of university students memorizing the Qur’an. An explanatory sequential mixed-methods design was employed. The quantitative phase involved 54 respondents selected through total sampling using a Likert-scale questionnaire, while the qualitative phase involved nine participants selected purposively and examined through observation, semi-structured interviews, and documentation. Quantitative data were analyzed using simple linear regression, whereas qualitative data were analyzed through thematic analysis and validated using source and technique triangulation. The findings show that self-regulated learning significantly influenced resilience, with a significance value of less than 0.001. The analysis also produced an R value of 0.857 and an R² value of 0.734, indicating that self-regulated learning contributed 73.4% to students’ resilience. Qualitative findings reveal that students with strong self-regulated learning were able to set memorization targets, manage learning strategies and time, maintain motivation, and evaluate their memorization process, enabling them to remain disciplined, adaptive, and persistent in facing challenges. The study concludes that self-regulated learning plays a critical role in strengthening the resilience of university students memorizing the Qur’an. These findings contribute to Islamic education and student development literature by highlighting self-regulated learning as a key psychological and learning-related factor in sustaining Qur’an memorization amid academic and social pressures.